2011
DOI: 10.1016/j.jphotochem.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic behavior of spironaphthoxazine in metal ion-containing solutions

Abstract: The isomerization and metal chelation of spironaphthoxazine (SNO) in ethanol solutions have been investigated by measuring the UV-vis absorption spectra as a function of time.The protonated species of merocyanine (MC), an isomer of SNO, was gradually formed in the solutions containing SNO and aluminum ions in the dark. The proton was provided by the reaction of the aluminum ions with a slight amount of water contained in the ethanol solvent.The protonated species was slowly transformed into the aluminum chelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…The band assigned to MCH + was observed at 530 nm and its intensity increased with time in the acidic SNO ethanol solution in which the molar ratio of SNO to H + was 3/1 as previously reported [24]. Fig.…”
Section: Reaction Of Sno With Acidsupporting
confidence: 82%
See 4 more Smart Citations
“…The band assigned to MCH + was observed at 530 nm and its intensity increased with time in the acidic SNO ethanol solution in which the molar ratio of SNO to H + was 3/1 as previously reported [24]. Fig.…”
Section: Reaction Of Sno With Acidsupporting
confidence: 82%
“…Under this condition, the reaction rates were faster and the amounts of products were greater than in the dark although the spectral peak positions and the patterns of increase and decrease in their intensities were similar to those in the dark. It was previously confirmed that SNO directly formed the MC-Al 3+ complex without forming the protonated species during the UV irradiation [24]. The protonation and aluminum chelation of SNO easily proceeded under the present conditions.…”
Section: Reaction Of Sno With Aluminum Ionsupporting
confidence: 72%
See 3 more Smart Citations